Predictors of Homonegativity in the United States and the Netherlands Using the Fifth Wave of the World Values Survey. Issue 10 (2nd October 2016) - Haney, Jolynn L.
ABSTRACT: Using data from the fifth wave of the World Values Survey (WVS), I investigated negative attitude toward homosexual individuals in two countries—the United States and the Netherlands—to determine how factors associated with homonegativity in the United States compare with factors associated with homonegativity in the Netherlands. Logistic regression of survey responses from 2, 299 participants from the United States ( n = 1, 249) and the Netherlands ( n = 1, 050) supported findings from previous research suggesting that homonegativity is more likely to occur in the United States than in the Netherlands, and that negative attitudes toward persons with AIDS and immigrants predicted homonegativity in both countries. Predictors of homonegativity in the United States included being male and being unemployed; in the Netherlands, being unhappy predicted homonegativity. How these findings inform social work policy and practice related to the lesbian, gay, bisexual, and transgender (LGBT) population, as well as suggestions for future research, are discussed.